المنهج الإصلاحي لجماعة الدعوة والتبليغ : دراسة تحليلية - سليمة، زاهر حامد زاهر محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The study aims at characterizing the methodology of reform adopted by Jamaat al-Da'wah wa al-Tabligh. It will bring to limelight the definition of Jamaat al-Da'wah wa al-Tabligh, its founder and historical milestone. The deliberation on the methodology of reform will include among others various spectrums of Tablighi reform, its influence with prophetic reform's methodology and also means of reform adopted in light of political, social and religious mileu surrounding the establishment of Jamaat itself. The study also accentuates on the positive and negative realms of the movement. A comprehensive grasp of the subject matter requires adopting mix methods of study which comprised of deductive, historical, as well as analytical methods. The study concludes that Jamaat Da'wah and Tabligh has emerged as a response to the plight faced by Muslims in politics, society and religion. The movement has introduced a unique way of contextualizing Islam among people, which is based on the principle of selfs spiritual reform, close relationship with God and man, purity of intention and willingness to sacrifice wealth, time and self for the sake of Da'wah, most importantly avoiding any involvement with any political and jurisprudential polemics .